1991
DOI: 10.1007/bf00917906
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell lysis by activated human neutrophils: Analysis of neutrophil-delivered oxidative attack and role of leukocyte function-associated antigen 1

Abstract: The lysis of tumor cells, and other nucleated mammalian cells, by neutrophilic polymorphonuclear leukocytes (PMNs) triggered by phorbol myristate acetate (PMA) represents a widely used model system to dissect the PMN cytolytic armamentarium, potentially responsible for the cell damage at tissue sites of PMN activation. Although oxidants are generally considered to be instrumental in the target lysis by PMNs, the mediators actually involved remain a matter of controversy. Moreover, other factors potentially cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 28 publications
0
38
0
4
Order By: Relevance
“…94,95 Furthermore, patients showing disease response to treatment have a significantly greater production of PMN oxidants, such as HOCl, which is regarded as instrumental in tumor cell lysis. 55,77 Evidence suggests that production of the tumoricidal long-lived oxidant HOCl, along with up-regulation of PMN surface integrins, may also contribute to the antineoplastic efficacy of infusional therapy with TNF-␣. [96][97][98] However, besides their involvement in the therapeutic efficacy of certain cytokines, PMNs may be partly responsible for the toxic side effects of high-dose systemic cytokine therapy.…”
Section: Pmns and Anticancer Therapy In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…94,95 Furthermore, patients showing disease response to treatment have a significantly greater production of PMN oxidants, such as HOCl, which is regarded as instrumental in tumor cell lysis. 55,77 Evidence suggests that production of the tumoricidal long-lived oxidant HOCl, along with up-regulation of PMN surface integrins, may also contribute to the antineoplastic efficacy of infusional therapy with TNF-␣. [96][97][98] However, besides their involvement in the therapeutic efficacy of certain cytokines, PMNs may be partly responsible for the toxic side effects of high-dose systemic cytokine therapy.…”
Section: Pmns and Anticancer Therapy In Humansmentioning
confidence: 99%
“…54 Recent dissection of the cytolytic armamentarium of PMNs has suggested a primary role for hypochlorous acid (HOCl) in mediating tumor cell lysis by activated PMNs after their leukocyte function-associated antigen 1-dependent recognition of the target cell surface. 55 Furthermore, a distinct adhesion pathway, mediated by CD11b/CD18 up-regulation on activated PMNs, enables these cells to adhere to the vascular endothelium and create a subjacent microenvironment, allowing accumulation of oxidants and proteolytic enzymes at local concentrations sufficient to cause endothelial damage and matrix degradation. 56 In addition, PMN-released HOCl reacts with primary amines to form relatively stable chloramines with immunostimulatory properties.…”
Section: Pmn-induced Tumor Destructionmentioning
confidence: 99%
“…Since lactoferrin has potent ability to inhibit neutrophil migration, it seems likely that in tumors in which neutrophils play a supportive role, limitation of neutrophil infiltration through lactoferrin administration could be therapeutically beneficial. However, in tumors in which neutrophils are absent, we propose that, given the known antitumor effects of neutrophils (68)(69)(70)(71), encouragement of neutrophil infiltration through inhibition of lactoferrin may effect tumor destruction. Our results might predict that tumors in which apoptosis is prominent would produce lactoferrin in situ.…”
Section: Figurementioning
confidence: 99%
“…The mAbs BU15 (anti-CD11c), 84H10 (anti-CD54), and 4B4 (anti-CD29) were obtained from Beckman Coulter (Fullerton, CA). The blocking F(abЈ) 2 anti-CD102 mAb CBR-IC2/2 and anti-CD54 MHCD54F were from Caltag Laboratories (Burlingame, CA). Anti-CD50 mAb 76205.11 was purchased from R&D Systems (Minneapolis, MN).…”
Section: Reagentsmentioning
confidence: 99%
“…1). Their tumoricidal ability requires close contact with the tumor cells (2,3) and is associated with the production of reactive oxygen species, proteases, membrane-perforating agents, and soluble mediators of cell killing such as TNF-␣, IL-1␤, and IFNs (1). However, several independent studies have demonstrated that PMNs enhance the metastatic potential of tumor cells.…”
mentioning
confidence: 99%